2006
DOI: 10.1249/00003677-200604000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Time Course of Arterial Vascular Adaptations to Inactivity in Humans

Abstract: We demonstrate that extensive arterial vascular adaptations occur within 3-8 wk of inactivity in humans. We put forth the hypothesis that the diameter decrease represents an adaptation to a lack of variation in peak shear stress. Furthermore, an enhanced flow-mediated dilation in deconditioned arteries implies that functional vascular adaptations to inactivity are not simply the inverse of adaptations to exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 14 publications
4
41
0
Order By: Relevance
“…A number of mechanisms may contribute to cardiovascular deconditioning induced by DI: circulatory blood volume loss [20,21], impaired baroreflex sensitivity [22,23], autonomic dysfunction [22,24], increased venous compliance [21] enforced by decreased muscle tone [25], macrovascular [26] and microvascular [27] impairment promoted by physical inactivity and prolonged decrease of shear stress forces [28], myocardial impairment, hormonal changes, vestibular changes, or metabolic changes. Hypovolemia appears to be the major contributor for the observed rapid cardiovascular impairment in DI.…”
Section: Hypovolemia As Major Reason For Di-induced Cardiovascular Dementioning
confidence: 99%
“…A number of mechanisms may contribute to cardiovascular deconditioning induced by DI: circulatory blood volume loss [20,21], impaired baroreflex sensitivity [22,23], autonomic dysfunction [22,24], increased venous compliance [21] enforced by decreased muscle tone [25], macrovascular [26] and microvascular [27] impairment promoted by physical inactivity and prolonged decrease of shear stress forces [28], myocardial impairment, hormonal changes, vestibular changes, or metabolic changes. Hypovolemia appears to be the major contributor for the observed rapid cardiovascular impairment in DI.…”
Section: Hypovolemia As Major Reason For Di-induced Cardiovascular Dementioning
confidence: 99%
“…A number of studies have investigated the effect of inactivity on arterial dynamics in AB individuals, and these have been reviewed elsewhere. 119,120 Briefly, using horizontal bed rest as a model for inactivity, it has been reported that vessel diameter and blood flow are reduced, endothelial function is impaired and shear stress and peripheral resistance are increased. 82 It has also been shown that the structural alterations resulting from inactivity can be ameliorated with regular physical activity, 70 and that such changes occur within days or weeks of the onset of exercise.…”
Section: Deconditioning-induced Alterations In Vasculaturementioning
confidence: 99%
“…However, previous studies have recruited similar or smaller groups and have typically examined the effects of 5 to 7 days of bed rest only. 47,48 Because the magnitude of physical inactivity is time dependent, 49 60 days clearly resulted in a large impact on the vasculature. The profound stimulus of complete bed rest, 49 combined with the excellent reproducibility of our technique, 22 allowed us to detect these important findings in a relatively small group of participants.…”
Section: Van Duijnhoven Et Al Bed Rest and Conduit Artery Remodeling 243mentioning
confidence: 99%
“…47,48 Because the magnitude of physical inactivity is time dependent, 49 60 days clearly resulted in a large impact on the vasculature. The profound stimulus of complete bed rest, 49 combined with the excellent reproducibility of our technique, 22 allowed us to detect these important findings in a relatively small group of participants. It should also be emphasized that bed rest such as that used in the present experiment does not represent a sedentary lifestyle, and our findings cannot necessarily be extrapolated to those of sedentary, yet ambulatory, individuals.…”
Section: Van Duijnhoven Et Al Bed Rest and Conduit Artery Remodeling 243mentioning
confidence: 99%